The Role of Entrepreneurial Leadership in MSME Digital Business Development - Awaludin; Amirudin (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Micro, small, and medium enterprises in Medan City face challenges in adopting digital technologies due to limited digital literacy and infrastructure, yet entrepreneurial leadership offers a pathway to overcome these barriers. This study aims to examine the characteristics, challenges, and strategies faced by MSMEs, as well as to analyze the impact of entrepreneurial leadership on digital business development in the digital economy era. Using a descriptive qualitative approach, the research involves in-depth interviews, participatory observations, and documentation with 10 enterprise owners in Medan who have adopted digital tools for at least three years. The findings reveal that proactive, innovative, and adaptive leadership enables these enterprises to use platforms like social media and e-commerce, enhancing market reach and transaction efficiency. However, inconsistent revenue growth highlights the need for sustained content strategies and advanced training, with only half of the enterprises reporting steady turnover increases. Challenges include low digital literacy, unstable internet, and limited human resources. Government and community support, through training and digital networks, strengthens these efforts. The study concludes that entrepreneurial leadership is vital for digital transformation, but success requires ongoing training and collaboration with stakeholders to build a robust digital ecosystem for enterprises in Medan.